Association between virulence profile and fluoroquinolone resistance in Escherichia coli isolated from dogs and cats in China - Xiaoqiang Liu; Haixia Liu; Yinqian Li; Caiju Hao (Journal of Infection in Developing Countries)
Introduction: Escherichia coli is not only a commensal organism in humans and animals, but also a causative agent of diarrhea and extraintestinal infections. Information about the relationship between population structure, virulence gene profiles, and fluoroquinolone resistance of E. coli in dogs and cats in China is limited. Methodology: A total of 174 pathogenic and commensal E. coli isolates were evaluated in terms of phylogenetic group, virulence gene profile, sequence types (STs), and fluoroquinolone susceptibility. Results: A total of 46.6% of isolates belonged to phylogenetic group B2. Isolates displayed high resistance to tetracycline (82.2%), amoxicillin/clavulanic acid (73.6%), gentamicin (62.1%), and enrofloxacin (60.9%). fimH (81.6%) was the most prevalent virulence gene, and 83.9% of isolates contained one or more investigated virulence genes. The majority of the investigated virulence genes were more prevalent in fluoroquinolone-susceptible isolates and pathogenic isolates. Multilocus sequence typing (MLST) showed that E. coli isolates analyzed were assigned to 65 STs. Among of them, pathogenic-resistant and pathogenic-susceptible isolates had 44 and 10 STs, respectively, while there were 8 and 3 STs in the commensal resistant and susceptible isolates, respectively. Conclusions: Phylogenetic group B2 was the dominant group, accounting for 46.6% of the isolates. Pathogenic isolates and fluoroquinolone-susceptible isolates possessed more virulence genes. Pathogenic isolates and fluoroquinolone-resistant isolates exhibited high population diversity, and pandemic clone ST131 appeared in 9.8% of isolates.